Muslim Spiritual Happiness Scale: The Instrument Development and Validation - Fitri Sukmawati; Sumin Sumin; Edi Istiyono; Widhiastuti Widhiastuti; Isyatul Mardiyati (Islamic Guidance and Counseling Journal, 2022)
The western happiness scale measures those material aspects, so it will not be objective when applied in low-income countries. Furthermore, Countries with high happiness ratings, which may ignore the importance of spirituality, have significantly higher rates of depression and suicide. Islam is the highest source of spirituality for its adherents. They believe happiness cannot only be measured by the material aspect and ignore the spiritual part. This study aims to develop a happiness scale that measures Muslim spiritual-material aspects. We used a development research approach to design an instrument based on the thoughts of Abdullah bin Abbas, test its validity, and estimate its reliability. The authors found Seven sub-scales and thirty-one valid items for Muslim spiritual happiness. The current instrument of happiness can be used to measure the spiritual happiness of Muslims. The authors expected that these findings encourage other researchers to improve the current version and develop a better and more valid instrument.